Structural, photocatalytic and electroconductive properties of bismuth-substituted CaMoO4 - Mikhaylovskaya, Zoya A.; Abrahams, Isaac; Petrova, Sofia A.; Buyanova, ElenaS; Tarakina, Nadezda V.; Piankova, Diana V.; Morozova, Maria V. (Journal of solid state chemistry, 2020)
The Ca1−3xBi2xФxMoO4 system (0.025 ​≤ ​x ​≤ ​0.30, where Ф represents cation vacancies) was synthesized and studied. The 0.025 ​= ​x ​≤ ​0.15 compositions show a tetragonal defect scheelite structure. Powder X-ray and neutron diffraction patterns for compositions with 0.15 ​< ​x ​≤ ​0.225 exhibit a tetragonal supercell with asup ​≈ ​√5a, csup ​≈ ​c where a and c are the tetragonal scheelite cell parameters. Transmission electron microscopy shows that Ca0.4Bi0.4MoO4, crystals consist of three crystallographic domains: (1) defect scheelite; (2) tetragonal superlattice and (3) incommensurately modulated. Photocatalytic properties were studied using Rhodamine B water solutions under UV light. Catalytic activity increases with increasing Bi content. The conductivity of 0.15 ​< ​x ​≤ ​0.225 compositions is 10−7 to 10−8 ​S ​cm−1 in the range 500–650 ​°C, while compositions in the range 0.025 ​= ​x ​≤ ​0.15 show conductivity values from 10−3 to 10−8 ​S ​cm−1 from 500 to 800 ​°C. [Display omitted] •Ca1−3xBi2xФxMoO4 (0.025 ​≤ ​x ​≤ ​0.15) shows a defect scheelite structure.•Ca1−3xBi2xФxMoO4 (0.15 ​< ​x ​≤ ​0.225) exhibits a supercell with asup ​≈ ​√5a, csup ​≈ ​c.•Three types of domains in Ca0.4Bi0.4MoO4 microcrystals were found by TEM.•The photocatalytic activity of Ca1−3xBi2xФxMoO4 for RhB oxidation increases with x.